An additional record of Fejervarya manoharani Garg and Biju from the Western Ghats with a description of its complete mitochondrial genome - Kiran, S. Kumar; Anoop, V. S.; Sivakumar, K. C.; Dinesh, Raghunathan; Mano, J. P.; Kaushik, Deuti; Sanil, George (Zootaxa, 2017)
An additional sighting of newly described frog species, Fejervarya manoharani Garg and Biju, outside of the type locality along with their morphological data is reported herewith. We are also providing the whole DNA sequence of the mitochondrial genome with its gene organization as additional data to distinguish this species from its congeners. The mitogenome of F. manoharani was 17,654 bp in length. It contains 38 genes including two rRNAs, 23 tRNAs, 13 protein-coding genes and a control region. Similar to other dicroglossid frogs, a tandem duplication of tRNAMet was found. The ND5 gene was located at the 3' end of the control region like in three other Fejervarya species for which mitogenomic data are available. A rearrangement of four tRNA genes, namely Leucine, Threonine, Proline, and Phenylalanine, between ND5 and 12S rRNA, differing from other Fejervarya species, was also observed.